Research on Resource Allocation based on Clustering in Femtocell Networks - Ding Kai; Liu Zhanjun; Zhou Shiyan; Ran Weiyi; Li Wei (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Aiming at the problem that existing femtocell base station searching the optimal clustering scheme based on the clustering resource allocation algorithm is complex. we propose that building an conflict graph and adjacency matrix before clustering to calculate the number of clusters needed for FBS group by using the adaptive clustering heuristic algorithm. We follow maximization the sum of the FBS distances in the cluster and group the femtocell base stations to narrow the search range to reduce the computational complexity. In order to achieve different business types service, based on the above clustering algorithm, this paper proposes a new method that using the weighted energy efficiency, which including the user interruption and the network spectral efficiency as a fitness function of the power control scheme to solve the problem. The simulation results show that the same rate requirement reduces the complexity, while the same complexity increases the user's average rate.